KARAKTERISTIK SERAT TANDAN KOSONG KELAPA SAWIT (TKKS) DENGAN PERLAKUAN PEREBUSAN DAN PENGUKUSAN - Lya Agustina; Udiantoro Udiantoro; Abdul Halim (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Empty Fruit Bunches (EFB) is a byproduct of the processing of palm oil utilization is still limited. One Palm Oil Mill (POM) in South Kalimantan, with a production capacity of 800 tons/day can produce 176 tonnes of EFB/day. In Indonesia, oil palm empty fruit bunches be used as paper pulp, fiberboard and furniture filler material volume. The aim of this study was to analyze the characteristics and fiber yield as a byproduct of industrial EFB CPO (Crude Palm Oil). The method used in this study is the experimental method with a Randomized Block Design (RBD) single factor. Namely the treatment of boiling, steaming and without treatment (control), each of which carried 9 repetitions.Results showed that the EFB fiber characteristics which include tensile strength, density, length and diameter did not significantly affect the treatment of color while boiling and steaming. EFB fiber yield obtained does not affect the treatment of boiling and steaming.